Lewis & Clark the journey of the Corps of Discovery - Burns, Ken, 1953-; Duncan, Dayton; Barnes, Paul.; Ewers, Erik.; Holbrook, Hal.; Florentine Films; WETA-TV (Television station : Washington, D.C.); PBS DVD (Firm); Warner Home Video (Firm) ([U.S.?] : PBS DVD ; Hollywood, Calif. : Distributed by Paramount Home Entertainment, 2004)
Tells the story of the most important expedition in American history, led by Captains Meriwether Lewis and William Clark. Includes the stories of the young army men, French-Canadian boatmen, Clark's African-American slave, and the Shoshone woman named Sacagawea who went with them.
Originally broadcast on PBS, Nov. 10, 1997.
Special features: Ken Burns: Making history; a Conversation with Ken Burns; the making of Lewis & Clark featurette; Charlie Rose interviews with producers Ken Burns, Dayton Duncan and author Stephen Ambrose.
Editors, Paul Barnes, Erik Ewers ; narrator, Hal Holbrook.
Not rated.
DVD, region 1, full screen presentation; Dolby Digital.
Closed captioned.
Keywords: Lewis, Meriwether, -- 1774-1809.; Clark, William, -- 1770-1838.; DVD-Video discs; Video recordings for hard of hearing people; West (U.S.) -- Description and travel; United States -- Discovery and exploration; Television programs; Video recordings for hard of hearing people